Dynamic changes in human THP-1-derived M1-to-M2 macrophage polarization during Thelazia callipaeda MIF induction - Yin, Changzhu; Cai, Juan; Gou, Yanting; Li, Di; Tang, Hongri; Wang, Lingjun; Liu, Hui; Luo, Bo (Frontiers in Immunology, 2023)
Innate immunity plays an important role in helminth infection, such as the direction of macrophage polarization. This study aims to establish that the recombinant protein of Thelazia callipaeda macrophage migration inhibitory factor (T.cp-MIF) induces THP-1-derived macrophages to undergo M1 to M2 type dynamic polarization, as well as to identify the molecular mechanisms regulating such polarization. This will lay a foundation for further understanding the role of parasite-derived T.cp-MIF in the immune interaction mechanism between parasites and hosts. Flow cytometry and real-time quantitative PCR demonstrated that macrophages exhibited an M1 to M2 type dynamic polarization process under T.cp-MIF induction. To further understand the molecular mechanism behind this dynamic polarization, the onset time points of M1 and M2 type polarization, namely 12 h and 36 h, were selected for differential transcriptomic analysis. The results showed macrophage dynamic polarization was mainly closely related to NF-κB and PI3K signaling pathways. Further, Western blot and real-time quantitative PCR technology were used to confirm the existence of a corresponding decrease in the protein and mRNA expression of the downstream signaling pathway upon treatment with different inhibitors. Interestingly, there was an increase in protein and mRNA expression of M1-type proteins and cytokines after the use of PI3K inhibitors, suggesting that the polarization state tends to favor the M1 type after M2 type inhibition. In conclusion, the dynamic polarization mechanism of T.cp-MIF-induced human THP-1-derived macrophages from M1 to M2 type is related to the binding of TLR4. It can first affect the M1 type polarization of macrophages by activating its downstream NF-κB pathway. Activation of the PI3K/Akt pathway and inhibition of NF-κB phosphorylation affects the M2 type polarization of macrophages.